Environment Code Embodying Climate Action: A Qualitative PESTEL Analysis of Ilocos Sur - Bensen Alex Urbano Pola (Science and Technology - Recent Updates and Future Prospects Vol. 6, 2024)
The study sought to assess the Code to determine if the current ideals of mitigating the causes of climate change are precisely aligned to the attainment of the Intended Nationally Determined Contribution (INDC), and realization of Sustainable Development Goals 13 - Climate Action (SDG). The process of the study is to derive a situational understanding and implementation analysis of the Code, to develop a matrix of proposed policies as the basis for creating guidelines for restoring the forest and coastal conditions of the locality. The study used qualitative thematic and PESTEL analyses particularly the hybrid approach via structural and value types of coding. The themes necessitate the occurrence of a triangular effect that brings forth a reflexive identity for the amendment or development of the Code to a more responsive policy towards sustainable climate conditions. The immediate management implications to PGIS are inherently implied in the weaknesses of the Code, which are seen in the lack of necessary provisions that call for immediate action and the improvement of the implementation process. The primordial recommendation is to research and examine the remaining Articles of the Code to gain a holistic understanding of the needed inclusions prior to appropriate actions by PGIS legislative officials. This will provide an all-inclusive scrutiny of the areas of weaknesses, strengths, opportunities, and threats of the Code, and unleashes the best approach to fighting climate change.